Room‐Temperature Nanoseconds Spin Relaxation in WTe(2) and MoTe(2) Thin Films - Wang, Qisheng (Adv Sci (Weinh), 2018)
The Weyl semimetal WTe(2) and MoTe(2) show great potential in generating large spin currents since they possess topologically protected spin‐polarized states and can carry a very large current density. In addition, the intrinsic non‐centrosymmetry of WTe(2) and MoTe(2) endows with a unique property of crystal symmetry‐controlled spin–orbit torques. An important question to be answered for developing spintronic devices is how spins relax in WTe(2) and MoTe(2). Here, a room‐temperature spin relaxation time of 1.2 ns (0.4 ns) in WTe(2) (MoTe(2)) thin film using the time‐resolved Kerr rotation (TRKR) is reported. Based on ab initio calculation, a mechanism of long‐lived spin polarization resulting from a large spin splitting around the bottom of the conduction band, low electron–hole recombination rate, and suppression of backscattering required by time‐reversal and lattice symmetry operation is identified. In addition, it is found that the spin polarization is firmly pinned along the strong internal out‐of‐plane magnetic field induced by large spin splitting. This work provides an insight into the physical origin of long‐lived spin polarization in Weyl semimetals, which could be useful to manipulate spins for a long time at room temperature.